2019
DOI: 10.1177/1756287219887656
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors affecting semen improvement after microsurgical subinguinal varicocelectomy: which subfertile patients benefit from surgery?

Abstract: Background:The exact mechanism of varicocele-related infertility is still elusive, therefore, the current challenges for its management lie in determining which patients stand to benefit most from surgical correction. The authors aimed to assess the clinical factors affecting semen improvement after left microsurgical subinguinal varicocelectomy (MSV) in relation to patient age, ultrasound varicocele grading (USVG), and presence of a right subclinical varicocele (RSV).Methods:From 2010 to 2017 a total of 228 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
2
16
0
2
Order By: Relevance
“…Conversely, Palmisano et al. (2019) reported mean sperm concentration improved after varicocelectomy in ⩾35‐year‐old patients. Since our patient group was in a narrow age range, we found that age does not affect post‐operative sperm parameters.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Conversely, Palmisano et al. (2019) reported mean sperm concentration improved after varicocelectomy in ⩾35‐year‐old patients. Since our patient group was in a narrow age range, we found that age does not affect post‐operative sperm parameters.…”
Section: Discussionmentioning
confidence: 97%
“…Palmisano et al. (2019), in their study with 228 patients who underwent varicocelectomy, found that patients with a grade 3 ultrasound varicocele grading (USVG) presented a three times greater probability of sperm concentration improvement compared with patients with a lower USVG. Infertile patients with high‐grade varicocele benefit more from intervention; still, a higher grade is more often associated with testicular atrophy, resulting in a loss of potential sperm recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, indications prompting repair of left-sided clinical varicoceles in adolescents have varied, but have included persistent testicular size discrepancy, abnormal semen parameters, and testicular discomfort or pain. 13 14 15 Varicocele repair during the adolescent period represents a preemptive attempt to enhance peripubertal testicular growth and potentially function in the hope of improving future fertility potential.…”
Section: Introductionmentioning
confidence: 99%
“…Частота рецидивов варикоцеле после флебэктомии с применением пахового доступа достигала, по данным EAU, 13,3 %. В то же время микрохирургическая эктомия ВРВ семенного канатика через субингвинальный доступ характеризуется наименьшей частотой осложнений (0,8-4,0 %) и считается сейчас «золотым стандартом» в лечении варикоцеле, в том числе при наличии клинических показаний к те рапии мужского бесплодия, обусловленного патозоо спермией [2][3][4][5][6].…”
unclassified
“…По данным С. И. Гамидова и соавт., консервативная монотерапия варикоцеле минерально-витаминными комплексами улучшала параметры спермы на 30 % [6]. По мнению же многих исследователей, наиболее эф-фективно (на 70 %) улучшает параметры спермы при варикоцеле микрохирургическая эктомия ВРВ семенного канатика [3][4][5]. Однако хирургическая коррекция варикоцеле в случае нарушения сперматогенеза не всегда способствует восстановлению мужской фертиль ности, в связи с чем актуальным становится вопрос об эффективности комбинированного лечения патозооспермии, включающего флебэктомию и консервативную терапию в послеоперационном периоде с целью улучшения морфофункциональных показателей сперматозоидов.…”
unclassified